Guillain-Barré-Strohl syndrome and COVID-19: Case report and literature review - Diez-Porras, Laura (Neuromuscul Disord, 2020)
In recent months, the new beta-coronavirus has caused a pandemic with symptoms affecting mainly the respiratory system. It is established that the virus may play a neurotropic role and in recent months several cases of Guillain-Barré-Strohl syndrome (GBS) have been reported in patients infected with COVID-19. We report the case of a 54-year-old patient with acute demyelinating polyneuropathy during infection by SARS-CoV-2 who progressed clinically to require assisted ventilation. After several weeks of specific symptomatic treatment, the patient had a favorable outcome. In conclusion, despite being a rare complication, we think it is important to consider the possibility of diffuse involvement of the peripheral nervous system in patients with COVID-19 to adjust clinical monitoring and treatment in these cases.